The folk in Filipino Catholic Christianity - Flores, Ma. Crisanta Nelmida (2021)
Accessible online through this link: https://journals.upd.edu.ph/index.php/Banwaan/article/view/8554/7491
Keywords: Catholicism; Christianity; Paganism; Idols and images